Evaluasi Strategi Komunikasi Visual Terhadap Kemampuan Menghafal Mufrodat pada Anak ADHD (Attention Deficit Hyperactive Disorder) di LPPA Ar Roja’ Surakarta - Mufidah Mufidah (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2021)
This research is motivated by the need to use appropriate strategies for teaching children with special needs (cwsn) who have attention deficit hyperactivity disorder (adhd). It also aims to understand the crucial importance of evaluating the challenges and difficulties encountered during the learning process of children with special needs. The method used in this study is a qualitative method with evaluative analysis. The choice of a qualitative approach in this research is intended to explore data and information more deeply, in order to understand the perspectives and views of teachers, parents, and therapists. The findings of the study can be summarized as follows: 1. Teaching arabic vocabulary (mufrodat) using visual communication strategies is considered quite effective, as children with adhd can easily understand material presented in visual form, such as images or real objects. 2. In visual communication-based learning, children may appear as if they are not looking at the object being shown. They tend to avoid direct eye contact with the object or image but may glance briefly. However, when the material is practiced and reviewed, they are able to recall what was learned. 3. The effectiveness of visual communication strategies in teaching arabic vocabulary to children with adhd is seen in their improved memorization patterns. The children begin to recall more vocabulary that they have learned and are able to remember it during review sessions later on.